Editor's Note. - Martínez Torres, Javier (International Journal of Interactive Multimedia and Artificial Intelligence, 2021)
The International Journal of Interactive Multimedia and Artificial Intelligence – IJIMAI (ISSN 1989-1660) provides an interdisciplinary forum in which scientists and professionals can share their research results and report new advances on Artificial Intelligence (AI) tools or tools that use AI with interactive multimedia techniques. The present volume, June volume, consists of 24 articles of diverse applications of great impact in different fields, always having as a common element the use of artificial intelligence techniques or mathematical models with an artificial intelligence base. As is logical, COVID is present in several manuscripts of this volume, always focused on the prediction and estimation of the presence of the disease. In addition to this expected presence, there are manuscripts of a semantic or syntactic analysis nature as well as works in the field of management and recommender systems. It is also worth mentioning several works in the field of video compression and signal processing. Of course, the Internet of Things and text analysis for several applications could not be missed in this volume. Finally, different manuscripts on usability and satisfaction, investments, solar panels, malware detection, video analysis, audio analysis and learning can also be found in this volume.